CAN System Engineering From Theory to Practical Applications - Lawrenz, Wolfhard; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
The controller area network (CAN) microcontroller communication protocol is now ubiquitous in a staggeringly wide range of transportation and industrial control applications. This fully revised and updated new edition addresses the various challenges and open questions relating to CAN communication networks. Opening with a short introduction into the fundamentals of CAN, the book then examines the problems and solutions for the physical layout of networks, including EMC issues and topology layout. Additionally, a discussion of quality issues with a particular focus on test techniques is presented. Each chapter features a collection of illuminating insights and detailed technical information supplied by a selection of internationally-regarded experts from industry and academia. Topics and features: Presents thorough coverage of architectures, implementations and application of CAN transceiver, data link layer and so-called higher layer software Explains CAN EMC characteristics and countermeasures, as well as how to design CAN networks Demonstrates how to practically apply and test CAN systems Includes examples of real networks from diverse applications in automotive engineering, avionics, and home heating technology Includes a glossary of abbreviations, and a useful bibliography This comprehensive text will be an invaluable guide/reference for electronic engineers working with industrial control systems. Prof. Dr. Wolfhard Lawrenz is the former founder and director of C&S Group GmbH. He has extensive worldwide experience and recognition in working with CAN techniques with companies ranging from automotive manufacturers and suppliers to semiconductor manufacturers, as well as international standardization committees such as ISO and SAE.
CAN Basic Architectures -- Physical Layer -- Data Link Layer Implementation -- Higher Level Protocols -- Applications -- Testing.
Keywords: Computer science; Computer network architectures; Computer Science; Computer Systems Organization and Communication Networks; Control, Robotics, Mechatronics